Resource allocation and rationing in nursing care: A discussion paper - Scott, P Anne; Harvey, Clare; Felzmann, Heike; Suhonen, Riitta; Habermann, Monika; Halvorsen, Kristin; Christiansen, Karin; Toffoli, Luisa; Papastavrou, Evridiki (My University, 2019)
Driven by interests in workforce planning and patient safety, a growing body of literature has begun to identify the reality and the prevalence of missed nursing care, also specified as care left undone, rationed care or unfinished care. Empirical studies and conceptual considerations have focused on structural issues such as staffing, as well as on outcome issues – missed care/unfinished care. Philosophical and ethical aspects of unfinished care are largely unexplored. Thus, while internationally studies highlight instances of covert rationing/missed care/care left undone – suggesting that nurses, in certain contexts, are actively engaged in rationing care – in terms of the nursing and nursing ethics literature, there appears to be a dearth of explicit decision-making frameworks within which to consider rationing of nursing care. In reality, the assumption of policy makers and health service managers is that nurses will continue to provide full care – despite reducing staffing levels and increased patient turnover, dependency and complexity of care. Often, it would appear that rationing/missed care/nursing care left undone is a direct response to overwhelming demands on the nursing resource in specific contexts. A discussion of resource allocation and rationing in nursing therefore seems timely. The aim of this discussion paper is to consider the ethical dimension of issues of resource allocation and rationing as they relate to nursing care and the distribution of the nursing resource.
Keywords: Care left undone; Missed nursing care; Nursing care; Rationing; Resource allocation